SEFH National Survey-2019: general characteristics, staffing, material resources and information systems in Spain's hospital pharmacy departments - Montserrat Pérez-Encinas; Ana Lozano-Blázquez; Javier García-Pellicer; Inmaculada Torre-Lloveras; José Luis Poveda-Andrés; Miguel Ángel Calleja-Hernández (Elsevier, 2020)
Objective: To publicize the results regarding the general characteristics, human resources, materials and information systems of Spanish hospital pharmacy departments arising from SEFH's 2019 Survey on the Situation of Spanish Hospital Pharmacy Departments. Method: An online questionnaire was sent to the heads of the 368 hospital pharmacy departments affiliated to SEFH. The questionnaire included 77 questions grouped into 8 dimensions. The information was collected between March and September 2019. Results: The overall response rate was 54.3%. Sixty-nine percent of hospitals were public and the most commonly reported hospital size was 101-250 beds. Nine percent of responding hospitals remained open round the clock and 57.5% did not offer a continued care service. A total of 41.9% of hospitals dispensed medications to outpatients in the afternoon and 52.7% of hospital pharmacy departments were accredited to some quality standard. The mean number of specialist pharmacists per pharmacy Department was 5.34 (SD: 6.22); 47% of pharmacists spent at least half their working day in a clinical unit. Hospital pharmacy departments had a mean of 0.3 (SD: 0.7) or 0:9 (SD: 1.4) automated storage and dispensing carousels, depending on whether they were horizontal or vertical, respectively. A total of 16.1% of beds were assisted by automated dispensing systems, a figure that reached 33.5% in hospitals with more than 1,000 beds. Three percent of hospital pharmacy departments had a robotized system for compounding chemotherapy medications and 24.8% had a raceability and safety system. Smart infusion pumps were used by 21.4% of hospitals. Electronic prescriptions were implemented in 98.8% of hospitals for inpatients and in 62% for outpatients. Conclusions: Spanish hospital pharmacy departments face a shortage of specialist pharmacists, although incorporation of such professionals to clinical units has doubled in the last few years. There has been an increase in the level of automation of the logistic processes involved in medication dispensing, but there is still significant room for improvement in the area of robotized dispensing and compounding traceability systems. This data could play an invaluable role in the design of future action plans.